TINDAK PIDANA PENCUCIAN UANG DALAM PERSPEKTIF HUKUM POSITIF DAN ISLAM: ANALISIS TEORETIS DAN STUDI KASUS DI INDONESIA (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Money laundering is a transnational crime that poses a significant threat to economic stability, the integrity of financial systems, and the rule of law in a country. This study aims to analyze the effectiveness of Indonesia’s positive legal framework in combating money laundering, examine relevant case studies, and explore the Islamic legal perspective on such practices. Using a normative juridical and qualitative-descriptive approach, this research analyzes Law No. 8 of 2010 along with scholarly literature and Islamic fatwas. The findings indicate that despite the establishment of regulations and institutions like the Financial Transaction Reports and Analysis Center (PPATK), law enforcement faces technical, technological, and inter-agency coordination challenges. Meanwhile, Islamic law, based on the principles of maqashid sharia, emphasizes justice, transparency, and the prohibition of unlawfully acquired wealth. Integrating positive law and sharia-based frameworks offers an alternative strategy to strengthen anti-money laundering efforts in Indonesia.